A Cognitive-Behavioral Treatment for Irritable Bowel Syndrome Using Interoceptive Exposure to Visceral Sensations - Craske, Michelle G. (2011)
BACKGROUND: Irritable bowel syndrome (IBS) is a chronic and debilitating medical condition with few efficacious pharmacological or psychosocial treatment options available. Evidence suggests that visceral anxiety may be implicated in IBS onset and severity. Thus, cognitive behavioral treatment (CBT) that targets visceral anxiety may alleviate IBS symptoms. METHODS: The current study examined the efficacy of a CBT protocol for the treatment of IBS which directly targeted visceral sensations. Participants (N = 110) were randomized to receive 10 sessions of either: (a) CBT with interoceptive exposure to visceral sensations (IE); (b) stress management (SM); or (c) an attention control (AC), and were assessed at baseline, mid-treatment, post-treatment, and follow-up sessions. RESULTS: Consistent with hypotheses, the IE group outperformed AC on several indices of outcome, and outperformed SM in some domains. No differences were observed between SM and AC. The results suggest that IE may be a particularly efficacious treatment for IBS. CONCLUSIONS: Implications for research and clinical practice are discussed.